2018
DOI: 10.5755/j01.erem.74.1.19779
|View full text |Cite
|
Sign up to set email alerts
|

Waste as energy source in EU action plan for the circular economy

Abstract: Investigations present that changes in municipal solid waste composition and properties correlate with the size and density of the municipal solid waste type, that mechanical pre-treatment including separation by weight and size can be useful for preparation of refuse derived fuel (RDF) material and solid recovered fuel (SRF) used for energy recovery. The authors determine the parameters of separated components of the coarse fraction (lower heating value, moisture, ash content, carbon, nitrogen, hydrogen, sulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…As it is shown in [10], in recent years, interest in burning the high-calorific fraction to obtain electricity has arisen in many countries worldwide. The reasons considered by the authors explain the increased interest in waste incineration for energy: depletion of natural resources, increased waste generated lack of landfill space, reduced greenhouse gases emissions, and reduced dependence on imported energy sources.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…As it is shown in [10], in recent years, interest in burning the high-calorific fraction to obtain electricity has arisen in many countries worldwide. The reasons considered by the authors explain the increased interest in waste incineration for energy: depletion of natural resources, increased waste generated lack of landfill space, reduced greenhouse gases emissions, and reduced dependence on imported energy sources.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Considering construction material based on red mud, this material has been investigated on special cement production [104][105][106][107][108]. Using wastes or secondary raw materials in construction is essential to face the diminution of primary raw materials and promote the circular economy [109]. This application is fundamental since it desires huge material volume.…”
Section: Research 231 Possible Applicationsmentioning
confidence: 99%
“…This approach follows the EU Action Plan of the Circular Economy which focuses on keeping values of raw materials within the economy for as long as possible and, of course, with the minimalization of the produced waste (Hagelüken, 2016). A complex research oriented on food waste reuse can be identified in the past few years (Arina & Bendere, 2018, Bhargava, 2020, Zhao et al, 2021. However, there is an emerging trend in the research focused on the use of waste created within the food processing industry (Yusoff, 2006).…”
Section: Introductionmentioning
confidence: 99%